DNA barcoding survey of Trichoderma diversity in soil and litter of the Amazonian rainforest reveals Trichoderma strigosellun sp, nov. and other species (2013)
ABSTRACT: The diversity of Trichoderma (Hypocreales, Ascomycota) colonizing leaf litter as well as the rhizosphere of Garcinia macrophylla (Clusiaceae) was investigated in primary and secondary rain forests in Colombian Amazonia. DNA barcoding of 107 strains based on the internal transcribed spacers 1 and 2 (ITS1 and 2) of the ribosomal RNA gene cluster and the partial sequence of the translation elongation factor 1 alpha (tef1) gene revealed that the diversity of Trichoderma was dominated (71 %) by three common cosmopolitan species, namely Trichoderma harzianum sensu lato (41 %), Trichoderma spirale (17 %) and Trichoderma koningiopsis (13 %). Four ITS 1 and 2 phylotypes (13 strains) could not be identified with certainty. Multigene phylogenetic analysis and phenotype profiling of four strains with an ITS1 and 2 phylotype similar to Trichoderma strigosum revealed a new sister species of the latter that is described here as Trichoderma strigosellum sp. nov. Sequence similarity searches revealed that this species also occurs in soils of Malaysia and Cameroon, suggesting a pantropical distribution.